Spatially‐Modulated Silicon Interface Energetics Via Hydrogen Plasma‐Assisted Atomic Layer Deposition of Ultrathin Alumina. Issue 6 (16th December 2022) - Henning, Alex; Bartl, Johannes D.; Wolz, Lukas; Christis, Maximilian; Rauh, Felix; Bissolo, Michele; Grünleitner, Theresa; Eichhorn, Johanna; Zeller, Patrick; Amati, Matteo; Gregoratti, Luca; Finley, Jonathan J.; et al.
Abstract: Atomic layer deposition (ALD) is a key technique for the continued scaling of semiconductor devices, which increasingly relies on scalable processes for interface manipulation of structured surfaces on the atomic level. While ALD allows the synthesis of conformal films with utmost control over the thickness, atomically‐defined closed coatings and surface modifications are challenging to achieve because of 3D growth during nucleation. Here, a route is presented toward the sub‐nanometer thin and continuous aluminum oxide (AlOx ) coatings on silicon substrates for the spatial control of the surface charge density and interface energetics. Trimethylaluminum in combination with remote hydrogen plasma is used instead of a gas‐phase oxidant for the transformation of silicon dioxide (SiO2 ) into alumina. Depending on the number of ALD cycles, the SiO2 can be partially or fully transformed, which is exploited to deposit ultrathin AlOx layers in selected regions defined by lithographic patterning. The resulting patterned surfaces are characterized by lateral AlOx /SiO2 interfaces possessing 0.3 nm step heights and surface potential steps exceeding 0.4 V. In addition, the introduction of fixed negative charges of 9 × 10 12 cm −2 enables modulation of the surface band bending, which is relevant to the field‐effect passivation of silicon and low‐impedance charge transfer across contact interfaces. Abstract : Atomic layer deposition (ALD) is a key technique for the continued scaling of semiconductor devices, but atomically‐defined coatings and surface modifications are challenging to achieve. This work describes an ALD process that allows the creation of ultimately thin microscopic patterns on silicon substrates with defined surface charge densities, through the transformation of the surface oxide layer into alumina.